Hiram Bingham papers - Bingham, Hiram, 1875-1956.
Correspondence, reports, memoranda, clippings and other items dealing with the war in China, the Nanking Incident (Nan-ching shih, China), Chinese trade-unions, Japanese proposals for Shanghai, American arms embargo, and Bingham's trip to China.
Explorer, educator, lecturer, and governor of and U.S. senator from Connecticut.
Collection material in English.
Keywords: Labor unions -- China; Sino-Japanese Conflict, 1931-1933.; China -- Description and travel; China -- Foreign relations -- Japan; China -- Foreign relations -- United States; Japan -- Foreign relations -- China; Nan-ching shih (China) -- History; Shanghai (China) -- History; United States -- Foreign relations -- China; Educators; Explorers; Governors -- Connecticut; Lecturers; Senators, U.S. Congress -- Connecticut